2020
DOI: 10.1097/qad.0000000000002488
|View full text |Cite
|
Sign up to set email alerts
|

TIGIT is upregulated by HIV-1 infection and marks a highly functional adaptive and mature subset of natural killer cells

Abstract: Objective: Our objective was to investigate the mechanisms that govern natural killer (NK)-cell responses to HIV, with a focus on specific receptor--ligand interactions involved in HIV recognition by NK cells. Design and Methods: We first performed a mass cytometry-based screen of NK-cell receptor expression patterns in healthy controls and HIV+ individuals. We then focused mechanistic studies on the expression and function of T cell immunoreceptor with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 72 publications
0
51
2
Order By: Relevance
“…Among Kenyan adults, TIGIT expression was downregulated on CD56 dim cells from QFT + individuals, compared with QFT − individuals. Although no previously published studies have comprehensively evaluated TIGIT on NK cells in the setting of human Mtb infection, increased TIGIT expression on NK cells has been reported in studies of HIVinfected individuals, compared with HIV-uninfected individuals (Yin et al, 2018;Motamedi et al, 2019;Vendrame et al, 2020), indicating that TIGIT expression on NK cells may be modulated in the setting of chronic infection. Moreover, the level of expression of TIGIT on human NK cells has been associated with NK cell functional heterogeneity in healthy adults (Wang et al, 2015), and blockade of TIGIT has been reported to increase NK cell effector functions (Stanietsky et al, 2009;Wang et al, 2015;Zhang et al, 2018), thus providing rationale for exploring TIGIT as a potential immunotherapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Among Kenyan adults, TIGIT expression was downregulated on CD56 dim cells from QFT + individuals, compared with QFT − individuals. Although no previously published studies have comprehensively evaluated TIGIT on NK cells in the setting of human Mtb infection, increased TIGIT expression on NK cells has been reported in studies of HIVinfected individuals, compared with HIV-uninfected individuals (Yin et al, 2018;Motamedi et al, 2019;Vendrame et al, 2020), indicating that TIGIT expression on NK cells may be modulated in the setting of chronic infection. Moreover, the level of expression of TIGIT on human NK cells has been associated with NK cell functional heterogeneity in healthy adults (Wang et al, 2015), and blockade of TIGIT has been reported to increase NK cell effector functions (Stanietsky et al, 2009;Wang et al, 2015;Zhang et al, 2018), thus providing rationale for exploring TIGIT as a potential immunotherapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells were purified from PBMCs by magnetic-activated isolation via negative selection (Miltenyi, Bergisch Gladbach, Germany) and stained for mass cytometry as described previously [40], using CyTOF Panel 1 (S1 Table). All antibodies were conjugated using MaxPar1 ×8 labeling kits (Fluidigm, South San Francisco, CA, USA).…”
Section: Mass Cytometry For Nk Cell Profiling Of Hesn and Healthy Benmentioning
confidence: 99%
“…Markers noted to have poor staining were excluded from subsequent analyses (FAS-L, Ki-67, KIR2DS2 and CXCR6 for Panel 1; CD11a and KIR2DS2 for Panel 2). Serial negative gating was used to identify NK cells, as described [40] (S1 Fig). Normalized signal intensities were transformed using the inverse hyperbolic sine (asinh) function with a cofactor equal to 5 to account for heteroskedasticity, prior to subsequent analyses.…”
Section: Plos Onementioning
confidence: 99%
“…This is particularly relevant as our study used IL-2 activated NK cells. TIGIT + NK cells have also been previously implicated in HIV control -TIGIT expansion is markedly enhanced on NK cells in untreated HIV infection (Yin et al, 2018;Vendrame et al, 2020). We also recently demonstrated that TIGIT expression marks a population of NK cells with an adaptive phenotype with greater functional activity against HIV-infected cells as well as other stimuli (Vendrame et al, 2020).…”
Section: Discussionmentioning
confidence: 76%
“…CD56 neg NK cells are functionally impaired and thought to be exhausted, demonstrating reduced cytotoxicity and IFN-ɣ production (Hu et al, 1995;Mavilio et al, 2005;Milush et al, 2013). In addition, the expression of the inhibitory receptor Siglec-7 (Brunetta et al, 2009), as well as the expression of the activating receptors NKp30, NKp44 and NKp46 (Mavilio et al, 2003), are decreased in chronic, viraemic HIV infection, whereas the expression of the inhibitory receptor TIGIT is increased (Yin et al, 2018;Vendrame et al, 2020). After treatment with antiretroviral therapy (ART), the patterns of CD56 + and CD56 neg NK cell subsets are restored to levels similar to seronegative, healthy individuals (Mavilio et al, 2005).…”
Section: Introductionmentioning
confidence: 99%